Вступительное слово - ПоддьяковАлександр Николаевич (Психология. Журнал Высшей школы экономики, 2014)
The Psychology Journal of Higher School of Economics continues the tradition of special issues on a specific topic. In this issue we offer to the reader a block of articles on Psychology and Mathematics. This topic has not yet appeared as an independent theme in our special issues, though it has been addressed in some issues in different topics as well as in various articles 1. Development is the major topic of the four articles on psychology and mathematics, presented in this special issue: development at different levels, with different subjects of activity (behavior), in various areas that aroused interest of mathematical psychologists. The first two articles are presented in Russian, the other two — in English. It reflects the new editorial policy of the journal that seeks to create the best conditions for cooperation of domestic and foreign researchers. T.Savchenko and G.Golovina discuss the historical development of mathematical psychology and its role in the humanities. The paper formulates the subject and object of mathematical psychology, it described the classification of its historically arising and current models. It also gives a generalized and realistic description of the status of mathematical psychology in the system of the Russian psychological education and analyzes the achievements and difficulties of mathematical psychology at the present stage. A.Vinogradov shows the main directions of socio-cognitive theory of personality over the past decades and discusses the reasons why it is not as successful in competing with the theory of personality traits as it might be. He justifies the idea that social and cognitive theory needs to develop its own system of statistical methods, the research design and psychometrics. He offers own original approaches to the problem both at the level of a common methodology and of specific decisions concerning charting studies. It is important to draw attention to a common problem, different aspects of which are addressed by T.Savchenko, G.Golovina and A.Vinogradov, that is the need to improve the explanatory and predictive power of mathematical models of behavior in different situations. In terms of the outstanding philosopher, mathematician and mathematical psychologist, V.Lefebvre, who is referred to in another context by T.Savchenko and G.Golovina, psycho-diagnostics is the study of a system comparable to the researcher for excellence. This position makes one of the challenges for mathematical psychology. Among other things, it leads to the following assumption: even the best psychologists, armed with the best developments will be faced with the fact that the subject under study does not fit the model created by another subject, and turns out to be richer. Working with both the average and maximum values, “extreme examples” is one of the most important sources of development of methods of mathematical psychology. As one of the directions of the development A.Vinogradov sees the individually oriented psychometrics which provides tools to describe the quality of statistical models at the individual level, as well as the development of the psychological theory of situations with an adequate conceptual apparatus. Two other articles in the issue are devoted to the study of psychology of understanding mathematics itself and the attitude to it. The article by T.Havenson and E.Oryel continues the meaningful but brief analysis of the problems with the mathematical education of students in humanities, which ends the article of N.Savchenko and G.Golovina. T.Havenson and E.Oryel consider the relationship between understanding (or not understanding) statistics by sociology students, the attitude to it and persoanl characteristics of these students, their academic motivation and perseverance. Presenting this study we should mention the use of the statistics attitude questionnaire adapted for Russian students (SATS-36) with six subscales that enabled (using also other tools) to obtain important data about the attitude towards mathematics and its understanding by various groups of future professionals in humanities. A.Krichevets, A.Schwartz and D.Chumachenko represent the study of eye movements dynamics in solving mathematical problems on Cartesian coordinates by people differing in knowledge and understanding of mathematics (school students, first-year students of non-mathematical specialties and mathematical faculties graduates). It is shown that the logic of the perceptual actions change observed with the increasing mathematical competence, reflects the logic of the historical formation of the Cartesian plane as a visual model in mathematics. This study is one of the most important evidence of possibilities of the interaction of general methodology of cultural and historical approach, highly competent researchers in the study domain (in this case in mathematics and its history) and the art of specific experiments using the most modern equipment and methods of mathematical processing data. Of course, the four articles presented cannot cover all the problems of interaction between psychology and mathematics. It means that the journal will continue to systematically refer to this topic. Enjoy the reading!(Footnote 1) Here we should mention the article by A.Belyanin Mathematical Psychology as a Branch of Economics (Psychology. Journal of Higher School of Economics. 2004. # 3), which goes far beyond the actual economics and mathematical psychology into a broader value-philosophical and methodological context.)